Well-being : In search of a good life? - Searle, Beverley A. (Book collections on Project MUSE., 2008)
"We are often told that 'money can't buy happiness'. But if money is not the answer then what is? This book considers this question by examining empirical data stretching back almost 10 years. Whereas previous concerns of individual well-being have been drawn towards the negative outcomes of life experiences, this book provides a new approach by directly addressing the circumstances under which high subjective well-being is experienced, often with surprising results."--